ANALISIS THEORY OF PLANNED BEHAVIOUR DAN PENGETAHUAN TERHADAP NIAT BERINFAQ JAMAAH MAJELIS TAKLIM KECAMATAN SUKOMANUNGGAL SURABAYA - Robbi Rodliyya Zahro; Sunan Fanani (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of the Theory of Planned Behavior and knowledge of the intention to invest in the assembly of the Taklim Muhammadiyah Sub-District of Sukomanunggal Surabaya. Primary data retrieval in this study used a questionnaire with a sample of 40 taklim assemblies in Sukomanunggal sub-district, Surabaya. The characteristics of the sample in this study were the pilgrims who attended the recitation in the assembly of taklim Muhammadiyah, Sukomanunggal, Surabaya. The sampling technique is Non-Probability Sampling and Simple Random Sampling. This study uses a quantitative approach with multiple linear regression analysis. The endogenous variable in this study is the intention to invest, while the exogenous variable used is part of the Theory of Planned Behavior which consists of attitudes, subjective norms, and Perceived Behavior Control and Knowledge. The results of this study indicate that simultaneously and partially attitudes, subjective norms, Perceived Behavior Control, and knowledge have a significant effect on the intention to invest in the assembly of taklim members of Muhammadiyah, Sukomanunggal District, Surabaya. Suggestions for further research to add to the scope of research subjects so that more general information can be obtained about related research, and using other variables outside of this research variable because it should be suspected that there are still several other factors that can influence intention to invest.Keywords: Theory Of Planned Behaviour, Knowledge, Infaq, IntentionREFFERENCESAbd Al-Rahman Al-Jazairi, Al-Fiqh ‘Ala Al-Madzahib Al-‘Arba’ah, (Bairut: Dar Al-Kutub Al-Ilmiyah, 2003), Juz. II, 140.Ajzen, I (1991).The Theory of Planned Behavior” Organizational Behavior and Human Decission Processes. Vol.50 No.2, PP179-211Ajzen, I (2005).Attitudes, Personality and Behavior.2nd Edition. Open University Press, New York. N.YAjzen, I. 1985. Attitude, Personality and Behavior. Open University Press :Milton keynesAlbari, 2002, Mengenal Perilaku Konsumen Melalui Penelitian Motivasi. Jurnal Siasat Bisnis Vol 1, No 7 (2002)Anwar, K.; Abu Bakar.; Harmaini. 2005. Hubungan antara Komitmen Beragama dengan Intensi Prososial Mahasiswa Fakultas Psikologi UIN SUSKA Riau. Jurnal Psikologi, Vol 1, No. 2, 69-77.A.W. Munawwir, Kamus Al-Munawwir, Pustaka ProgressifAzwar, S. (2007). Metode Penelitian.Yogyakarta : Pustaka PelajarBudiman, Wijaya. 2014. Purchase Intention of Counterfeit Products: The Role of Subjectivem Norm. International Journal of Marketing Studies. 4 (6); pp;95-102.Dewan Redaksi Ensiklopedi. 1994. Ensiklopedi Islam. Jakarta: PT. Ichtiar Baru Van Hoeve. Cetakan Keempat. Jilid 3Fishbein dan Ajzen, 1975. Belief, Attitude, Intentions and Behavior: an introduction to theory and research. California: Addison-Wesley Publishing Company, Inc.Ghozali, Imam. 2007. Aplikasi Analisis Multivariate dengan program SPSS. Cetakan keempat.Semarang :Badan Penerbit Universitas DiponegoroHafidhuddin, Didin. 2002. Zakat dalam Perekonomian Modern. Jakarta: Gema Insani.Hakim, Lukman. Prinsip-Prinsip Ekonomi Islam. Surakarta: Erlangga. 2012.Jogiyanto, 2007. Sistem Informasi Keperilakuan. Edisi Revisi. Yogyakarta: Andi OffsetMachrus, Hawa’im dan Urip Purwono Pengkuran Perilaku berdasarkan Theory of Planned Behavior, INSAN Vol. 12 No. 01, April 2010 Mowen, John, C dan Michael Minor. 2002. Perilaku Konsumen. Jilid Kedua. Jakarta: Erlangga.Muhsin MK, Manajemen Majelis Taklim, Jakarta: Pustaka Intermasa, 2009Notoatmodjo, S. 2003. Pendidikan dan Perilaku Kesehatan. Jakarta: Rineka CiptaRakhmat, J. (2005). Metode Penelitian Komunikasi. Bandung: PT Remaja Rosdakarya.Schiffman, L.G. dan Kanuk, L.L. 2004. Perilaku Konsumen. Edisi ketujuh. Prentice Hall International.Sekaran, Uma. 2006. Metodologi Penelitian Untuk Bisnis. Jilid 1. Edisi 4. Salemba Empat, Jakarta.Sugiyono.2013. Metodee Penelitian Kuantitatif Kualitatif dan R&D. Cetakan ke-22. Bandung: Alfabet.